The Role of Corporate Governance on the Relationship between Intellectual Capital performance and Firm value: Pre and Post of MCCG 2017 in Malaysia - Saleh, Haider Mahdi; Abdul Rahman, Mara Ridhuan Che; Hasan, Mohamat Sabri; Ahmad, Azlina (International Journal of Psychosocial Rehabilitation, 2020)
In the age of knowledge economy, intellectual capital (IC) is gaining prominence in academic research and management practices owing to the fact that it is a significant contributor value creation. In order to achieve maximum value, it has been argued that corporate governance (CG) mechanism plays important role by enhancing the management of IC practice via effective control, measurement and reliable reporting of IC. Therefore, this study investigates the moderating effect of CG (characteristics board of directors and audit committee) on the association between (IC) performance and firm value. Further, the study compare CG practices pre and post the implementation of MCCG in 2017and determine the importance of reform CG code and the extent of its impact on the value of the company. This study utilised a sample of 88 largest listed firms in bursa Malaysia from 2015 to 2018. This study examined data before (2015 and 2016) and after (2017 and 2018) the revised MCCG 2017code. Findings of the study show a positive association between intellectual capital performance (VAIC) and firm value. Also, the result of study show the human capital efficiency (HCE) and structural capital efficiency (SCE) were positive associations with firm value, while Capital employed efficiency (CEE) was not significant. Regression result provide evidence that the CG practices are significantly moderate the relationship between VAIC and firm value. The study also reveals that the moderating effect of MCCG 2017 is stronger than MCCG 2012 on the relation, indicating that regulators’ efforts in reforming CG practice code are worthwhile in this context. It can be recommended that investment on human capital and structural capital is paramount to influences firm value. The findings provide empirical support for resource base view and agency theory where a better corporate governance mechanism contributes to the better association between IC management practices and firm value.